DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED ON BALINESSE CULTURE CONTEXTUAL IN GRAPHIC DESIGN LEARNING AT CLASS X MULTIMEDIA IN SMK NEGERI 1 SAWAN - Pujawan, Kadek Agus Hendra; Jaka Mahendr, I Gede (LPPM Undiksha, 2018)
The objectives to be achieved in this study were (1) to describe the design of interactive multimedia development based on Balinese culture on graphic design learning at class X Multimedia in SMK Negeri 1 Sawan. (2) to describe the responses of content experts, design experts and media experts to the development of interactive multimedia based on Balinese Culture contextual on graphic design learning at Class X Multimedia in SMK Negeri 1 Sawan. (3) to describe the response of the user / teacher teaching graphic design subjects to the development of interactive multimedia based on Balinese contextual culture on graphic design learning at Class X Multimedia in SMK Negeri 1 Sawan. (4) to describe the response of students in the form of individual trials, small group trials and field trials on the development of interactive multimedia based on Balinese Culture contextual on graphic design learning in Class X Multimedia in SMK Negeri 1 Sawan. The interactive multimedia development model based on Balinese cultural contextual learning graphic design used Dick & Carey model. In the process of designing multimedia products, content experts are required to adjust the material presented in interactive multimedia with the material provided at school, in this case the teacher is appointed as content expert, so the teacher's contribution in this study is to provide a syllabus of graphic design material. In addition to content experts, media experts and design experts are also needed to test the validity of interactive multimedia developed. After being valid, it will be implemented in school by giving a questionnaire to students whether the interactive multimedia developed in this study is suitable for use or not. The following are tests on aspects of display, graphics, program operation and grammar performed by media experts obtaining 85% of the calculation results in good qualifications. Tests on aspects of learning, curriculum and interface design conducted by learning design experts obtain a calculation of 89% in good qualifications. User/teacher responded well. Individual trials carried out received good responses. Small group trials obtained calculation results of 90% are in very good qualifications. Field trials that were carried out obtained a calculation of 87% in good qualifications.